METODE KESHAHIHAN HADITS “AL-MUSTADRAK” DALAM KITAB AL-MUSTADRAK ‘ALA SHAHIHAIN - Mohammad Fattah; Muridatul Qutsiyah; Indri Maryani (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
This research article examines the method of authenticity of the hadith